A versatile and efficient markerless gene disruption system for Acidithiobacillus thiooxidans: application for characterizing a copper tolerance related multicopper oxidase gene. (28th May 2014) - Wen, Qing; Liu, Xiangmei; Wang, Huiyan; Lin, Jianqun
Summary The acidophilic bioleaching bacteria can usually survive in high concentrations of copper ions because of their special living environment. However, little is known about the copper homeostatic mechanisms of Acidithiobacillus thiooxidans, an important member of bioleaching bacteria. Here, a putative multicopper oxidase gene (cueO) was detected from the draft genome of A. thiooxidans ATCC 19377. The transcriptional level of cueO in response to 10 mM CuSO4 was upregulated 25.01 ± 2.59 folds. The response of PcueO to copper was also detected and might be stimulated by a putative CueR protein. Then, by using the counter‐selectable marker lacZ and enhancing the expression of endonuclease I‐SceI with tac promoter, a modified markerless gene disruption system was developed and the cueO gene disruption mutant (ΔcueO) of A. thiooxidans was successfully constructed with a markedly improved second homologous recombination frequency of 0.28 ± 0.048. The ΔcueO mutant was more sensitive to external copper and nearly completely lost the phenoloxidase activity; however, the activity could be restored after complementing the cueO gene. All results suggest the close relation of cueO gene to copper tolerance in A. thiooxidans. In addition, the developed efficient markerless gene knockout method can also be introduced into other Acidithiobacillus strains.